Fatty Acid Oxidation Promotes Cardiomyocyte Proliferation Rate but Does Not Change Cardiomyocyte Number in Infant Mice - Cao, Tongtong; Liccardo, Daniela; LaCanna, Ryan; Zhang, Xiaoying; Lu, Rong; Finck, Brian N.; Leigh, Tani; Chen, Xiongwen; Drosatos, Konstantinos; Tian, Ying (Frontiers in Cell and Developmental Biology, 2019)
Cardiomyocyte proliferation accounts for the increase of cardiac muscle during fetal mammalian heart development. Shortly after birth, cardiomyocyte transits from hyperplasia to hypertrophic growth. Here, we have investigated the role of fatty acid β-oxidation in cardiomyocyte proliferation and hypertrophic growth during early postnatal life in mice. A transient wave of increased cell cycle activity of cardiomyocyte was observed between postnatal day 3 and 5, that proceeded as cardiomyocyte hypertrophic growth and maturation. Assessment of cardiomyocyte metabolism in neonatal mouse heart revealed a myocardial metabolic shift from glycolysis to fatty acid β-oxidation that coincided with the burst of cardiomyocyte cell cycle reactivation and hypertrophic growth. Inhibition of fatty acid β-oxidation metabolism in infant mouse heart delayed cardiomyocyte cell cycle exit, hypertrophic growth and maturation. By contrast, pharmacologic and genetic activation of PPARα, a major regulator of cardiac fatty acid metabolism, induced fatty acid β-oxidation and initially promoted cardiomyocyte proliferation rate in infant mice. As the cell cycle proceeded, activation of PPARα-mediated fatty acid β-oxidation promoted cardiomyocytes hypertrophic growth and maturation, which led to cell cycle exit. As a consequence, activation of PPARα-mediated fatty acid β-oxidation did not alter the total number of cardiomyocytes in infant mice. These findings indicate a unique role of fatty acid β-oxidation in regulating cardiomyocyte proliferation and hypertrophic growth in infant mice.